EVALUATION OF ANTIPYRETIC AND ANTIULCER ACTIVITY OF ETHANOLIC EXTRACT OF LEAVES OF TREMA ORIENTALIS L. IN ALBINO WISTAR RATS - VANITA G KANASE; JYOTI SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The purpose of the present study was aimed at evaluating the antipyretic and antiulcer activity on leaves of Trema orientalis L. (family Cannabaceae) on albino Wistar rats. The antipyretic and antiulcer activity of the ethanolic extract of the T. orientalis L. leaves in three different concentrations (100, 200, and 300 mg/kg) was compared with standard paracetamol and pantoprazole, which was evaluated by employing Brewer’s yeast-induced pyrexia and ethanol-induced ulcer model. The biochemical parameters such as the volume of gastric juice secretion, pH, total acidity, ulcer index, percentage protection, and lipid peroxidation were also studied. Methods: T. orientalis leaves were extracted with ethanol by the Soxhlet extraction method. The dried extract was used for further phytochemical and pharmacological analysis. The antipyretic effect was studied using Brewer’s yeast-induced pyrexia. The ethanol-induced ulcer model was used to study the antiulcer effect. Results: The percentage yield of ethanolic extract of T. orientalis leaves was found to be 6.71% w/w, respectively. The extract showed significant antipyretic and antiulcer effect when compared with standard paracetamol and pantoprazole. Conclusion: The ethanolic extract of T. orientalis has significant antipyretic and antiulcer action.